Writing the Ghetto : Class, Authorship and the Asian American Ethnic Enclave. - Chang, Yoonmee, 1970- (UPCC book collections on Project MUSE., 2010)
In the United States, perhaps no minority group is considered as "model" or successful as the Asian American community, which is often described as residing in positive-sounding "ethnic enclaves." Yoonmee Chang's Writing the Ghetto helps clarify the hidden or unspoken class inequalities faced by Asian Americans, while insightfully analyzing the effect such notions have had on their literary voices.